Patogenicidad de Metarhizium anisopliae (Deuteromycota: Hyphomycetes) sobre Heterotermes tenuis (Isoptera: Rhinotermitidae) en Hevea brasiliensis - STERLING-C., ARMANDO; GÓMEZ-M., CARLOS A.; CAMPO-J., ARY A. (Revista Colombiana de Entomología, 2011)
In the Colombian Amazon termites attack bare root stumps of the rubber tree Hevea brasiliensis. The objective of the study was to evaluate the pathogenicity of the fungus Metarhizium anisopliae on Heterotermes tenuis termites under laboratory conditions. The concentrations used were 1x101, 1x103, 3x105, 1x107 and 3x108 conidia/ml and the control (distilled sterile water). The dead insects were cleared with KOH at 10% and mounted on glass slides. Mortality was compared using Kaplan-Meier survival curves and the CL50 and TL50 were determined. The concentration of 3x108 conidia/ml was the most effective (100% of insects eliminated in six days). There were differences found among the six concentrations used in percent survival of H. tenuis (H5,81 =19.4; p < 0.05) and in the time (days) of survival (H4,60=14.0; p < 0.05). The CL50 was 9.64 x 103 conidia/ml after a time of six days. The TL50 was three days for the concentration of 3 x 108 conidia/ml. Under laboratory conditions M. anisopliae is very effective on H. tenuis, and for this reason its use under natural conditions should be considered in the integrated management of the termites that affect the cultivation of rubber trees in the Amazonian region. This study is the first report on the in vitro biocontrol of H. tenuis in H. brasiliensis.